Effect of pars plana vitrectomy on early and long-term intraocular pressure and its determinants - Ana Faria Pereira; Pedro Marques-Couto; Rita Teixeira-Martins; Amândio Rocha-Sousa; Pedro Alves-Faria; Joana R. Araújo (Scientific Reports)
Abstract To assess intraocular pressure (IOP) changes and the development of ocular hypertension (OH) following pars plana vitrectomy (PPV), evaluating short- and long-term outcomes and risk factors. This is a retrospective study of 216 patients (432 eyes) who underwent primary unilateral PPV between April 2018 and July 2020, with ≥ 12 months of follow-up. IOP in vitrectomized and fellow eyes was analyzed preoperatively, at 3 months, and at final visit. OH was defined as the need for IOP-lowering medication; IOP was also analyzed as a continuous variable. Baseline and intraoperative factors were evaluated using cohort and matched case–control designs. Median follow-up was 28 months. Early and late OH occurred in 28.2% and 15.3% of vitrectomized eyes. Retinal detachment (RD) increased the risk of early OH fourfold (OR 4.16; p < 0.001). Higher preoperative IOP in the fellow eye predicted both early (OR 1.17; p = 0.003) and late OH (OR 1.18; p = 0.007). Postoperatively, vitrectomized eyes had higher IOP at all timepoints. Glaucoma developed in 6.5% of vitrectomized vs. 1.4% of fellow eyes (p = 0.008). PPV is associated with sustained IOP elevation and increased OH risk. RD and fellow eye IOP are relevant predictors. Long-term monitoring is essential to prevent glaucoma, especially in high-risk patients.